Neurocognitive-Spiritual Based Psychopedagogy in Improving Working Memory and Emotional Intelligence in Muslim Students - Syafii, Muhammad Hisyam; Alaldaya, Rudyn; Purnomo, Halim; Azhari, Husain (Journal of Islamic Education and Ethics, 2025)
The current study addresses the limitations of contemporary educational frameworks that often compartmentalize cognitive, emotional, and spiritual domains, thereby hindering holistic student development. This study employed a qualitative methodology using a systematic literature review approach. Data were sourced from scholarly articles, neuroscience textbooks, and educational policy documents published between 2020–2025. Document analysis matrices and content analysis protocols were utilized to extract and synthesize conceptual frameworks. The validity of findings was ensured through triangulation, peer reviews, reflexive journaling, and audit trails, implemented across six systematic research stages. Findings reveal that integrating neurocognitive strategies with spiritual practices fosters synergistic brain changes. These include neuroplastic modifications in the prefrontal cortex and limbic system, improving executive functions and emotion regulation. Integrating transcendental meaning-making and attentional control significantly boosts information processing and emotional resilience in learning environments. The implications of this research extend to educational policy, curriculum design, and teacher training, offering a scientific and spiritual synthesis that enriches both pedagogical theory and practice. This model proposes a developmental framework for implementing tailored interventions from early childhood through adulthood, supporting lifelong cognitive-emotional growth grounded in spiritual values.